2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6610677
|View full text |Cite
|
Sign up to set email alerts
|

Metric learning for automatic sleep stage classification

Abstract: We introduce in this paper a metric learning approach for automatic sleep stage classification based on single-channel EEG data. We show that learning a global metric from training data instead of using the default Euclidean metric, the k-nearest neighbor classification rule outperforms state-of-the-art methods on Sleep-EDF dataset with various classification settings. The overall accuracy for Awake/Sleep and 4-class classification setting are 98.32% and 94.49% respectively. Furthermore, the superior accuracy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In shallow learning, meaningful features are extracted by humans drawing upon their knowledge of both signal processing and sleep stage scoring manual. The extracted features span in time, frequency, and time–frequency domains, including non-linear features 21 27 , 29 , 35 , 39 , 41 . Various classification models are utilized to classify these extracted features ranging from traditional machine learning models such as k-nearest neighbor (kNN) 35 , support vector machines (SVM) 21 , 27 , 33 , decision tree 25 , and random forest 24 , 29 , to artificial neural networks (ANNs), and deep learning models which excel in the feature-based approach 23 .…”
Section: Introductionmentioning
confidence: 99%
“…In shallow learning, meaningful features are extracted by humans drawing upon their knowledge of both signal processing and sleep stage scoring manual. The extracted features span in time, frequency, and time–frequency domains, including non-linear features 21 27 , 29 , 35 , 39 , 41 . Various classification models are utilized to classify these extracted features ranging from traditional machine learning models such as k-nearest neighbor (kNN) 35 , support vector machines (SVM) 21 , 27 , 33 , decision tree 25 , and random forest 24 , 29 , to artificial neural networks (ANNs), and deep learning models which excel in the feature-based approach 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning typically involves feature extraction and classification. Phan et al [10] extracted features from single-channel EEG signals and used the k nearest neighbor algorithm with the Mahalanobis distance for classification. The method performs well in addressing four types of sleep stage problems.…”
Section: Introductionmentioning
confidence: 99%
“…Extracted features have been classified using various algorithms, i.e. k-nearest neighbors [26,27], support vector machines [25,[28][29][30], ensemble classifiers [31][32][33], decision trees [27,34], artificial neural networks [25,29,35], and threshold-based classifiers [22][23][24]36]. These earlier works have demonstrated that automatic detection of arousals and sleep stages can be achieved by employing methods relying on handcrafted features.…”
Section: Introductionmentioning
confidence: 99%